Os espaços de atuação do bibliotecário: uso da competência informacional no Serviço de Informação ao Cidadão (SIC) - GOMES, Amanda Garcia (2021)
Presents a research on the role of the librarian in the Citizen Information Service (SIC) through the use of the Professional Information Literacy. The Information Literacy as a form of learning that favors the production of knowledge, stimulating research, developing skills, becomes essential for contemporary society. In this sense, the general objective was to analyze and demonstrate the librarian's activities outside the traditional work environment, as well as to show the competencies needed to work in the SIC in order to contribute to compliance with the Law on Access to Information (12,527 / 2011) and to promote access to information for citizens. Thus the specific objectives were to investigate the main conceptual notions about Informational Competence; to categorize the activities developed within the SIC; identify the profile of the professionals working in the SIC; to point out the main informational skills needed to act in the SIC and to know the trajectory of the creation of the SIC. The study was carried out in the General Audit of the state of Pará, specifically in the SIC of the institution, the technical procedure being used for bibliographic research, with the application of a questionaire with the SIC respondents. It is concluded that the insertion of the librarian in the SIC can be beneficial to Public Administration, because, due to the development and the use of the Information Literacy the professional is able to work in the SIC.